Synthesis of Ag-TiO2 nanomaterial for treatment of organic pollutants under visible light - Dieu Cam, Nguyen Thi; Thanh Tung, Mai Hung (Vietnam Journal of Chemistry, 2017)
In this study, the sol-gel synthesis method was employed for the preparation of silver-doped TiO2 nanomaterial from potassium fluorotitanate and silver nitrate. The silver can be incorporated by direct calcination of the sol-gel material decomposing silver nitrate to silver. The visible light absorption ability of Ag- TiO2 nanoparticles was investigated by means of UV-Vis measurement. Based on the UV-Vis spectra, the absorption in the visible light of the Ag-TiO2 was found to be improved and was shifted to longer wavelength. The XPS spectra indicated that the elements detected were titanium, oxygen, and silver. Titanium and oxygen presented as Ti4+ and O2− and silver Ag existed in Ag (0) form. It is attributed to the fact that the silver is homogeneously dispersed throughout the material. The experimental results showed that the photocatalytic efficiency of Ag-TiO2 was better than prepared TiO2 under the same conditions for the photodegradation of methylene blue. Keywords. Potassium fluorotitanate, titanium dioxide, silver, photocatalysis, visible light